Associations Between Vascular Risk Factor and Perivascular Spaces in Adults with Intact Cognition, Mild Cognitive Impairment, and Dementia. - Rundek, Tatjana; Del Brutto, Victor; Goryawala, Mohammed; Dong, Chuanhui; Agudelo, Christian; Saporta, Anita Seixas; Merritt, Stacy; Camargo, Christian; Ariko, Taylor; Loewenstein, David A; Duara, Ranjan; Haq, Ihtsham (J Alzheimers Dis, 2022)
BACKGROUND: Perivascular spaces (PVS) are fluid-filled compartments surrounding small intracerebral vessels that transport fluid and clear waste. OBJECTIVE: We examined associations between PVS count, vascular and neurodegenerative risk factors, and cognitive status among the predominantly Hispanic participants of the FL-VIP Study of Alzheimer's Disease Risk. METHODS: Using brain MRI (n = 228), we counted PVS in single axial image through the basal ganglia (BG) and centrum semiovale (CSO). PVS per region were scored as 0 (none), 1 (<10), 2 (11-20), 3 (21-40), and 4 (>40). Generalized linear models examined PVS associations with vascular risk factors and a composite vascular comorbidity risk (VASCom) score. RESULTS: Our sample (mean age 72±8 years, 61% women, 60% Hispanic, mean education 15±4 years, 33% APOE4 carriers) was 59% hypertensive, 21% diabetic, 66% hypercholesteremic, and 30% obese. Mean VASCom score was 2.3±1.6. PVS scores ranged from 0-4 in the BG (mean 1.3±0.7) and CSO (mean 1.2±0.9), and 0-7 combined (mean 2.5±1.4). In multivariable regression models, BG PVS was associated with age (β= 0.03/year, p <  0.0001), Hispanic ethnicity (β= 0.29, p = 0.01), education (β= 0.04/year, p = 0.04), and coronary bypass surgery (β= 0.93, p = 0.02). CSO PVS only associated with age (β= 0.03/year, p <  0.01). APOE4 and amyloid-β were not associated with PVS. CONCLUSION: BG PVS may be a marker of subclinical cerebrovascular disease. Further research is needed to validate associations and identify mechanisms linking BG PVS and cerebrovascular disease markers. PVS may be a marker of neurodegeneration despite our negative preliminary findings and more research is warranted. The association between BG PVS and Hispanic ethnicity also requires further investigation.

Visualization of Focal Thinning of the Ganglion Cell-Inner Plexiform Layer in Patients with Mild Cognitive Impairment and Alzheimer's Disease. - Shao, Yi; Jiang, Hong; Wei, Yantao; Shi, Yingying; Shi, Ce; Wright, Clinton B; Sun, Xiaoyan; Vanner, Elizabeth A; Rodriguez, Anny D; Lam, Byron L; Rundek, Tatjana; Baumel, Barry S; et al. (J Alzheimers Dis, 2018)
BACKGROUND: A detailed analysis of the tomographic thickness of intraretinal layers may provide more information on neurodegeneration in patients with mild cognitive impairment (MCI) and Alzheimer's disease (AD). OBJECTIVE: The goal was to analyze tomographic thickness patterns of intraretinal layers in patients with AD andMCI. METHOD: Forty-nine patients (25 AD and 24 MCI) and 21 cognitively normal (CN) controls were imaged using ultra-high-resolution optical coherence tomography to obtain volumetric data centered on the fovea. The segmented intraretinal layers were retinal nerve fiber layer (RNFL), ganglion cell- inner plexiform layer (GCIPL), inner nuclear layer (INL), outer nuclear layer (ONL), outer plexiform layer (OPL), and retinal photoreceptor (PR), in addition to the total retinal thickness(TRT). RESULTS: The thickness differences were negative (thinning) mainly in TRT, RNFL, and GCIPL in both AD and MCI groups in comparison to CN, while the thickness differences were positive (thickening) mainly in ONL and PR in AD. GCIPL of AD and MCI was thinner in superior, nasal superior, and temporal superior quadrants, compared to CN (p < 0.05). GCIPL of the inner superior, inner nasal superior, inner temporal superior, and outer nasal superior sectors was significantly thinner in AD than CN (p < 0.05). GCIPL of the outer superior, inner temporal superior, outer nasal, and temporal superior sectors was significantly thinner in MCI than CN (p < 0.05). CONCLUSION: Focal thinning of the GCIPL was visualized and quantified by detailed partitions in AD and MCI, which provides specific information about neurodegeneration in MCI and AD.